The music education and teaching innovation using blockchain technology supported by artificial intelligence. (15th May 2023) - Yu, Honghao; Zou, Zhenqun
This exploration conducts innovative research on music education and teaching based on blockchain technology under AI and puts forward the general view of blockchain technology and its potential to contribute to future development. The essence, characteristics and development process of blockchain technology are discussed. Meanwhile, the thinking on the development of 'blockchain + education' is put forward, and the digital platform application of blockchain technology in music education and teaching is given. As the basis of system development, requirement analysis plays a crucial part in the subsequent system design and implementation. Analysing requirements can help people locate software functions more accurately and clearly. This exploration takes blockchain as the underlying technology support and relies on Fabric architecture to explore its application in digital education resource management.